2008
DOI: 10.1038/jes.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate exposure from food crops produced in the lower Colorado River region

Abstract: The Colorado River shows low levels of perchlorate derived from aerospace-and defense-related fuel industries once located near the Las Vegas Wash. At sufficiently high dosages perchlorate can disrupt thyroid function by inhibiting uptake of iodide. The Colorado River is the primary source of irrigation water for most food crops grown in Southern California and Southwestern Arizona. The objective of this study was to evaluate potential perchlorate exposure from food crops produced in the lower Colorado River r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…Consistent with findings from previous studies or perchlorate concentrations in foods (Jackson et al, 2005;Sanchez et al, 2005a;Sanchez et al, 2005b;Murray et al, 2008;Sanchez et al, 2008), results from our dietary simulations suggest that drinking water contamination accounts for a relatively small proportion of total population intake for reproductive-age women in the United States. As shown in Table 5, addition of reasonable assumed drinking water perchlorate distributions increases the central tendency (mean and median) estimates of national perchlorate intakes for reproductive-age women by between approximately 3 and 24%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with findings from previous studies or perchlorate concentrations in foods (Jackson et al, 2005;Sanchez et al, 2005a;Sanchez et al, 2005b;Murray et al, 2008;Sanchez et al, 2008), results from our dietary simulations suggest that drinking water contamination accounts for a relatively small proportion of total population intake for reproductive-age women in the United States. As shown in Table 5, addition of reasonable assumed drinking water perchlorate distributions increases the central tendency (mean and median) estimates of national perchlorate intakes for reproductive-age women by between approximately 3 and 24%.…”
Section: Discussionsupporting
confidence: 91%
“…Sanchez et al (2008) also used Monte Carlo analysis to estimate the perchlorate intake distribution for women aged Figure 2. Distribution of intra-day variability in perchlorate excretion (Greer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Perchlorate is formed in the atmosphere and can accumulate in the soils of arid regions (Dasgupta et al, 2005). Human exposure sources include contaminated drinking water and consumption of foods containing perchlorate; mainly, milk and high surface area plants such as leafy green vegetables (Murray et al, 2008; Sanchez et al, 2009). Human health concerns are related to the ability of perchlorate to competitively inhibit iodide uptake by the sodium-iodide symporter (NIS) of the thyroid gland (Dohan and Carrasco, 2003; Tonacchera et al, 2004).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Several researchers have demonstrated that certain veterinary antibiotics (e.g., florfenicol, trimethoprim, sulfamethazine, and enrofloxacin) can be taken up into food crops (e.g., wheat, corn, lettuce, barley, and potato) produced on manure-amended soils (22)(23)(24)(25) River to irrigate the approximately 400,000 ha of agricultural crops that are shipped nationally and internationally. Previous research has shown that the Colorado River is contaminated with low levels of perchlorate, and this contaminant can be detected in most agricultural commodities irrigated with this water (27,28). Macrolide antibiotics, pseudoephedrine, and illicit drugs have been identified in several municipal wastewater streams that discharge into the Colorado River (29).…”
Section: Introductionmentioning
confidence: 99%